Is China (really) slowing down? (American arguments against China’s further rise) - Cvetković, Vladimir; Kopanja, Mihajlo (Napredak, 2024)
Aware of the fact that China is a country whose rise points to the potential development of a sufficient level of ability to threaten American hegemony in the world, American authors are more and more frequently proposing a thesis that contemporary China is finally – slowly, but certainly – lagging behind in economic terms, which most likely leads to its return to the previous state – subordinacy on the global stage. The paper first presents the motive why the authors approach these considerations, while subsequently four groups of arguments of American authors against China’s further rise are identified (demographic trends, economic stagnation, institutional problems and collapse of globalization). Finally, through the discussion about the presented arguments, the third chapter gives an answer to the question whether China is really slowing down.
Keywords: hegemony; power; emerging powers; China; United States of America